Ayah dan Pendidikan Karakter Anak (Kajian Teks dan Konteks Perspektif Psikologi Pendidikan Islam): (Kajian Teks dan Konteks Perspektif Psikologi Pendidikan Islam) - Fitriah M. Suud; Aulia Rahmi; Fadhilah Fadhilah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2020)
The quality and quantity of mother and child attachment have often been discussing. Nevertheless, how the quality and quantity of the relationship between father and son, especially in shaping the child's personality is still rarely found. In the life of a child, sometimes role, the father is not felt because his figure is busy outside the home. Also provides an assumption that the father does not influence raising and educating children. The context of Islamic education in the family, the figure of the father, is the spiritual basis that underlies the role of parents in educating their children. A person's character formed early on. In this case, the role of the family is indeed very influential. The education of the father in the family is critical and is a fundamental pillar of character building for a child. From a child's father learns, hardened, brave, responsible, and easy to get along with the outside world. This study aims to present the role of fathers in shaping the character of children in terms of the study of texts and contexts through the field of psychology in Islamic education. The contextual study presents the latest research that proves the influence of the father in many ways for children and terms of the text of this study will present the primary sources of guidance for Muslim life, namely the Qur'an and the Hadith. So the implications given are not only normative but grounded to be able to broaden understanding and add new constructs for the implementation of the father and son relationship.